Temporal dynamics of lymphocytes in prostate cancer patients treated with proton therapy - Al-Hamami, Sarah Salih; Kurucz, Samuel; Vondráček, Vladimír; Pekar, Vladimír; Andrlík, Michal; Dědečková, Kateřina; Benešová, Iva; Haas, Alexandra; Ondrová, Barbora; Pasztorová, Andrea; Vítek, Pavel; Kubeš, Jiří (Frontiers in Oncology, 2025)
Radiotherapy can be both immunosuppressive and immunostimulatory. Radiation-induced lymphopenia (RIL) is an ongoing challenge in cancer treatment. We investigated weekly changes in the absolute lymphocyte count (ALC) during proton radiotherapy, evaluating the effects of different dosage, fractionation schedules, and pelvic node irradiation (PNI). Prostate cancer patients were prospectively chosen for this study, due to their relatively homogenous treatment plans. Treatment protocols were categorized into three groups: Group A (n=52) received 36.25 Gy/5-fractions, Group B (n=60) underwent 63 Gy/21-fractions and group C (n=69) received 63 Gy/21-fractions plus PNI. To account for individual characteristic differences, a new categorization method was made, according to the change in ALC relative to the baseline. Lymphopenia (ALC < 1000 K/μL) developed in 8%, 17% and 84% of patients in groups A, B, and C, respectively. An initial increase in ALC occurred in 44%, 47% and 28% of groups A, B and C, respectively, and declined with proceeding fractions. Patients with PNI had the most pronounced reduction in their ALC relative to the baseline. Increased dosage and fractionation led to a higher incidence of lymphopenia. Understanding which factors influence ALC in particle therapy is vital for leveraging the immune-enhancing effects of radiotherapy, while minimising its immunosuppressive impacts.